Can Transvaginal Cervical Elastography predict the success of induction of labor with oxytocin? - Halilzade, Inci; Halilzade, Mohammad İbrahim; Sert, Ümit Yasemin; Alkan, Mihriban; Keskin, Hüseyin Levent (Zeitschrift für Geburtshilfe und Neonatologie, 2023)
ObjectiveWe aimed to show whether elastography can be analternative, although the Bishop score used in the follow-up of labor induction success with oxytocin is a relative concept.Material and methods This prospective case-control study includes 56 cases admitted to a tertiary maternity hospital for induction between March and June 2019. Cervical elastography was applied to patients before induction. Induction success in pregnant women who underwent induction with oxytocin was accepted to be greater than Bishop 9. The cases were divided into two groups as successful (n=28) and unsuccessful (n=28) induction, and their elastosonographic findings were compared.ResultsIn 28 cases with successful induction (Bishop >9, and vaginal delivery occurred in 28), the mean stiffness of the cervix in measurements from four regions was 13.6 ±3.7 kPa in the measurement of the cervix with the elastography method before induction was started, while this value was measured as 14.9 ± 3.1 in cases where induction was unsuccessful (t- value: -1.321, p=0.194).Conclusions Our study showed that pre-induction stiffness of the cervix cannot predict the success of labor induction with oxytocin. More studies with larger samples are needed to arrive at a decent conclusion. In addition, results can be more assuring with the developing technique and sensitivity of elastography.
Keywords: labor induction; cervical elastography; oxytocin; pregnancy; bishop score